2020
DOI: 10.2139/ssrn.3631131
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Regulatory Responses to Covid-19 Pandemic: Balancing Banks’ Solvency and Contribution to Recovery

Abstract: We see spikes in unemployment rates and turbulence in the securities markets during the COVID-19 pandemic. Governments are responding with aggressive monetary expansions and large-scale economic relief plans. We discuss the implications on banks and the economy of prudential regulatory intervention to soften the treatment of non-performing loans and ease bank capital buffers. We apply these easing measures on a sample of Globally Systemically Important Banks (G-SIBs) and show that these banks can play a constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 9 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…The banking sector before the pandemic crisis was characterised by a high level of regulatory capital and liquidity as well as by the relatively good quality of credit portfolios. Consequently, Bitar and Tarazi (2020) concluded that on the eve of the pandemic G-SIBs banks had been adequately capitalized. The researchers analysed the effects of prudential regulatory intervention to soften the approach to non-performing loans and ease capital buffers on these banks and the economy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The banking sector before the pandemic crisis was characterised by a high level of regulatory capital and liquidity as well as by the relatively good quality of credit portfolios. Consequently, Bitar and Tarazi (2020) concluded that on the eve of the pandemic G-SIBs banks had been adequately capitalized. The researchers analysed the effects of prudential regulatory intervention to soften the approach to non-performing loans and ease capital buffers on these banks and the economy.…”
Section: Literature Reviewmentioning
confidence: 99%